Costume designing for the UP repertory company and the aesthetics of poverty - Rivera, Michelle Josephine Golez
This special problem "Costume Designing for the UP Repertory Company and the Aesthetics of Poverty" aims to find out if the practices of the UP Repertory Company with respect to costume designing can be considered as a practice of the aesthetics of poverty as presented by Brenda V. Fajardo in her monograph entitled "The Aesthetics of Poverty: Designing for Philippine Theater". Aesthetics of poverty being that sense of beauty which belongs to people who live in a condition of material deprivation as expressed by an artist. The study included seven plays that had been presented by the UP Repertory Company (UPRC) from 19897-1993. Three plays, Artists Daw, Fantasya and Set ng Mailap ang Tuwa, Pakipot and Liwanag, were collectively presented by the UPRC in a production entitled Kinse. The other plays were Mabini Girls, Lorena, Pagsabog ng Liwanag ang Pakikipagsapalaran ng Bagong Iskolar ng Bayan. These plays were chosen according to the abundance of available data. The data were summarized and analyzed. The findings of these study were based on materials gathered from the UPRC collection of publications and interviews with members and alumni of the UPRC. The results of the study showed that the UPRC practiced the aesthetics of poverty with respect to costume designing not as a matter of company policy but as a matter of circumstance. Circumstances being that the UPRC lacked proper funding. Kinse, for example included three plays but only a meager budget of five hundred pesos was allotted for the costumes of the three plays. This was because it was the only amount allotted by the budget.